Characterization of Petroleum Hydrocarbon Decomposing Fungi Isolated from Mangrove Rhizosphere - Nuni Gofar (JOURNAL OF TROPICAL SOILS, 2011)
The research was done to obtain the isolates of soil borne fungi isolated from mangrove rhizosphere which were capable of degrading petroleum hydrocarbon compounds. The soil samples were collected from South Sumatra mangrove forest which was contaminated by petroleum. The isolates obtained were selected based on their ability to survive, to grow and to degrade polycyclic aromatic hydrocarbons in medium containing petroleum residue. There were 3 isolates of soil borne hydrocarbonoclastic fungi which were able to degrade petroleum in vitro. The 3 isolates were identified as Aspergillus fumigates, A. parasiticus, and Chrysonilia sitophila. C. sitophila was the best isolate to decrease total petroleum hydrocarbon (TPH) from medium containing 5-20% petroleum residue.Keywords: Hydrocarbonoclastic fungi, hydrocarbon compounds, mangrove rhizosphere